The population of metropolitan Cape Town : a study in methodology - Ellis, Robin G (School of Architecture, Planning and Geomatics, 2020)
The object of this thesis is to study a selected number of demographic characteristics in a South African Metropolitan Situation by means of an analytical system. The demographic material will be coordinated and classified according to the system, for the purpose of assessing its utility and merit as a planning tool. In this assessment the Metropolitan Area of Cape Town will be used as an example. As a supplement to the main theme, a projection of the future population will be introduced.